In vitro antioxidant and anti-denaturation effects of Buglossoides purpurocaerulea (L.) I. M. Johnst. fruit extract. Issue 6 (19th March 2023) - Marrelli, Mariangela; Amodeo, Valentina; Puntillo, Domenico; Statti, Giancarlo; Conforti, Filomena
Abstract: Fruits from Buglossoides purpurocaerulea (L.) I. M. Johnst. were extracted with methanol through maceration. The phytochemical composition of obtained raw extract was investigated with gas chromatography-mass spectrometry (GC-MS) and high-performance thin layer chromatography (HPTLC) analyses. The total phenolic and flavonoid contents were also quantified and in vitro antioxidant activity was assessed using the DPPH assay and the β-carotene bleaching test. In order to verify the anti-arthritic potential, the raw extract was evaluated for its anti-denaturation effect on heat-treated bovine serum albumin (BSA), chosen as a protein model. Linoleic and α-linolenic acids were the most abundant identified apolar constituents. HPTLC analyses allowed the identification of rosmarinic acid. The sample showed a concentration-dependent antioxidant activity and it was also proven to be effective in preventing the heat-induced denaturation of BSA, with an IC50 value equal to 15.7 ± 0.5 µg/mL. Graphical Abstract: UF0001